Preparation of Carbopol 934 Based Ketorolac Tromethamine Buccal Mucoadhesive Film: In Vitro, Ex Vivo, and In Vivo Assessments. (11th October 2021) - Begum, M. Yasmin; Alqahtani, Ali; Ghazwani, Mohammed; Ramakrishna, M. M.; Hani, Umme; Atiya, Akhtar; Rahamathulla, Mohamed
Abstract : The goal of present investigation was to formulate and evaluate ketorolac tromethamine (KTM) mucoadhesive buccal films. The films were prepared by solvent evaporation method using PVP K30, HPMC K4M, HPMC K15M, carbopol 934, chitosan, and sodium alginate as polymers and propylene glycol as plasticizer. The films were evaluated for thickness, weight variation, folding endurance, surface pH, swelling index, in vitro residence time, in vitro diffusion, release kinetics, ex vivo permeation, in vitro-ex vivo correlation, and in vivo pharmacological activities such as anti-inflammatory and analgesic activity. Thickness, weight, drug content, and folding endurance were found to be uniform for the films. Surface pH was 6.85 ± 0.10, and swelling index was the highest (27.27 ± 0.37 ) for the best film containing carbopol 934 along with sodium alginate and PVP K 30 (formulation code F2). In vitro residence time was greater than 5 h, and in vitro % drug release was 98.71% for F2. It exhibited 55.49% of swelling inhibition at 5 h, and above 38.88% was maintained at even 8 h. The film F2 has shown maximum analgesic response of 17 sec at 5 h, and the response of 11 sec was maintained at even 8 h. The anti-inflammatory and analgesic effect of F2 was found be maximum while sustaining the effect for prolonged period when compared to free drug solution. Thus, KTM mucoadhesive buccal film containing carbopol 934, sodium alginate, and PVP K30 could be an effective alternative for conventional therapy with improved efficacy.